2012
DOI: 10.1258/ebm.2012.012168
|View full text |Cite
|
Sign up to set email alerts
|

Papaya epicarp extract protects against aluminum-induced neurotoxicity

Abstract: In a previous study, we demonstrated the ability of papaya epicarp extract (PEE) to protect against oxidative stress-induced insult in human SH-SY5Y neuronal cells in a mechanism that appeared to be by means of PEE potent antioxidant properties. To further understand this relationship, we examined the effect of PEE intervention on aluminum (Al)-induced cytotoxicity in SH-SY5Y cells. The results indicated that PEE was effective in protecting against Al-induced cell death in a dose-dependent manner. PEE restored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the brain tissue, FPP has been shown to have a neuroprotective effect from oxidative damage, from lipid peroxide level, and superoxide dismutase activity in iron-induced epileptic foci of rats [ 41 ]. At the neuronal level, FPP has been shown to have a neuroprotective action, to improve the oxidative status in human neuronal cells and to protect from insults by oxidative stress linked, for example, to the cytotoxicity by aluminum in neuronal cells [ 44 ]. Neuroprotective potential evaluated in an AD cell model showed that the toxicity of the A β can be significantly modulated and/or reduced by FPP.…”
Section: Resultsmentioning
confidence: 99%
“…In the brain tissue, FPP has been shown to have a neuroprotective effect from oxidative damage, from lipid peroxide level, and superoxide dismutase activity in iron-induced epileptic foci of rats [ 41 ]. At the neuronal level, FPP has been shown to have a neuroprotective action, to improve the oxidative status in human neuronal cells and to protect from insults by oxidative stress linked, for example, to the cytotoxicity by aluminum in neuronal cells [ 44 ]. Neuroprotective potential evaluated in an AD cell model showed that the toxicity of the A β can be significantly modulated and/or reduced by FPP.…”
Section: Resultsmentioning
confidence: 99%
“…Wound healing property of Carica papaya L (papaya) has been attributed to its high content of cystein endopeptidase, mineral nutrients and vitamins [ 1 3 ]. Wound healing potential of papaya based extracts is mainly linked to its anti-inflammatory and anti-oxidant properties [ 4 , 5 ]. We reported improved wound healing by unripe C. papaya when selenium (Se 2+ ) was added to the extract.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Also, catechin gallate esters from black tea and green tea have shown similar effects. [10] Although, there are many reports, which demonstrates that plant extracts can act as inhibitors of Ab aggregation and shows neuroprotection, [11][12][13][14] but their clinical success rate is poor. Therefore, in this manuscript we have tried to develop an extract for potential neuroprotective effect.…”
mentioning
confidence: 99%